A high efficient dual-output rectifier for piezoelectric energy harvesting - Yuen, Peng Wah; Chong, Gabriel; Ramiah, Harikrishnan (Elsevier, 2019)
In this paper, a high efficient active NMOS dual-output rectifier for piezoelectric energy harvesting (PEH) in CMOS technology is proposed. The rectifier adopts a cross-coupled active NMOS topology producing two output DC voltages. A DC-DC combiner at the rectifier's output is employed to sum the output DC voltages which improves the effective Voltage Conversion Efficiency (VCE) and Power Conversion Efficiency (PCE). Simulated on a standard 65-nm CMOS technology, the proposed rectifier achieves a VCE > 98% across a connected output load of Rrec > 9 kΩ and a peak PCE of ∼84% for Rrec = 12 kΩ. Compared to conventional piezoelectric rectifiers, the PCE of the proposed rectifier is significantly improved with comparative VCE performance.